Does intermunicipal cooperation increase efficiency? A conditional metafrontier approach for the Hessian wastewater sector. Issue 1 (2nd January 2018) - Blaeschke, Frédéric; Haug, Peter
ABSTRACT: This paper analyses the relationship between intermunicipal cooperation and efficiency of public service provision. Organisational arrangements of public service production, including self-provision, joint provision or contracting, affect incentives and internal transaction costs. Hence, cooperation gains from scale effects need to be balanced against technical inefficiencies. We analyse relative efficiency of wastewater disposal for German municipalities. We employ a conditional analysis in conjunction with a metafrontier approach to calculate relative efficiency measures and technology gap ratios controlling for organisational arrangements and further environmental variables. Jointly providing municipalities and contractor municipalities exhibit lower technical efficiency than self-providing and contracting municipalities. As confirmed by previous research, scale effects from cooperation and contracting apply to small municipalities primarily.